Los saberes de las plantas medicinales quechuas y su incorporación en las sesiones de aprendizaje en el área de ciencia y tecnología en la I.E. Niño Jesús de Turpo–Andahuaylas - Chircca Ccahuana, Esmeralda (2022)
In this thesis, we will focus on the approach to medicinal plants that were used in formal education in Peru, specifically in the Niño Jesús de Turpo kindergarten, Anadahuaylas, Apurimac. In this sense, we’ve addressed the incorporation of medicinal plants in the learning sessions of the science and technology area from the aforementioned educational institution. Thus, we will see that, in this institution, teachers use medicinal plants as a teaching medium in learning sessions. The presence of the elements of nature and their pedagogical incorporation to the initial level school is due to the need to generate new knowledge and to strengthen the ancestral knowledge of the Quechua habitants in the district of Turpo additionally, we have the influence of intercultural bilingual education produced in the school, particularly in teachers and parents. They are, at the end, the ones who decide about the phenomenon in question.